Dui’ Papenre Customary Law Reconstruction Based on Human Rights Values in the National Legal System - Syahril, Muh. Akbar Fhad; Asriyani, Arini; Krivins, Anatolijs (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
The purpose of this research is to reconstruct the practice of Dui' Papenre in Bugis marriage customs, ensuring it aligns with human rights values, particularly non-discrimination and equality, while preserving its cultural essence. This research also examines the harmonization between customary law, national law, and human rights principles, and proposes recommendations for legal reform. The research method used is normative law with a descriptive-analytical approach, supported by legislative, conceptual, and sociological perspectives. Data is sourced from legal documents and literature and analyzed qualitatively. The novelty of this research lies in its unique combination of analyzing Dui' Papenre from the perspectives of customary law, national law, and human rights, thereby filling a gap left by previous studies that have not comprehensively discussed this intersection. The findings reveal that the practice of Dui' Papenre still holds cultural value, but it often raises human rights concerns, particularly regarding the rights to form a family and non-discrimination, when the nominal value is disproportionate. The analysis shows that regulation through local regulations with reasonable nominal limits, dispute mechanisms, and community-based customary mediation can preserve traditions without violating human rights. In conclusion, the harmonization of customary law, national law, and human rights principles is key to ensuring that Dui' Papenre remains sustainable and fair. Transparent and participatory regulations will ensure that this tradition aligns with social justice and the protection of citizens' constitutional rights.